Ionospheric modeling for low frequency radioastronomy - Arora, Balwinder Singh Amrit Singh (Curtin University, 2016)
The research presented in this thesis aims to develop ionospheric corrections for calibration of future low frequency radio interferometers. GNSS data from ground stations close to the MRO were used to produce a model of the ionosphere. Comparisons of this model with ionospheric parameters derived from the MWA observations show good agreement. The installation of new GNSS stations in the vicinity of MRO would allow ionospheric modelling with higher spatial resolution.